Quantitative Analysis of the Protein Methylome Reveals PARP1 Methylation is involved in DNA Damage Response - Wang, Xinzhu; Mi, Shaojie; Zhao, Mingxin; Lu, Chen; Jia, Chenxi; Chen, Yali (Frontiers in Molecular Biosciences, 2022)
Protein methylation plays important roles in DNA damage response. To date, proteome-wide profiling of protein methylation upon DNA damage has been not reported yet. In this study, using HILIC affinity enrichment combined with MS analysis, we conducted a quantitative analysis of the methylated proteins in HEK293T cells in response to IR treatment. In total, 235 distinct methylation sites responding to IR treatment were identified, and 38% of them were previously unknown. Multiple RNA-binding proteins were differentially methylated upon DNA damage stress. Furthermore, we identified 14 novel methylation sites in DNA damage response-related proteins. Moreover, we validated the function of PARP1 K23 methylation in repairing IR-induced DNA lesions. K23 methylation deficiency sensitizes cancer cells to radiation and HU-induced replication stress. In addition, PARP1 K23 methylation participates in the resolution of stalled replication forks by regulating PARP1 binding to damaged forks. Taken together, this study generates a data resource for global protein methylation in response to IR-induced DNA damage and reveals a critical role of PARP1 K23 methylation in DNA repair.